Electronic relationship A study of legal principles - Raad Khza'al Abdulkrem Baker, (Islamic Sciences Journal, 2025)
Given the widespread decline in moral aspects of low-quality content as a result of the misuse of social media, it is necessary to shed light on these degeneracies through, the research aims to shed light on the concept of (cybersex), which is based on the illicit relationship between two parties through modern means of communication and their popular applications such as Telegram, WhatsApp, Messenger, and the like, and the violations that occur therein, whether through live broadcasting, sending silent images, or speaking through voice calls and conversations via messages, and explaining the legal ruling on it.